Associations between physical activity and sedentary time profiles transitions and changes in well-being in youth: The UP&DOWN longitudinal study. (March 2020) - Sánchez-Oliva, David; Esteban-Cornejo, Irene; Padilla-Moledo, Carmen; Pérez-Bey, Alejandro; Veiga, Óscar L.; Cabanas-Sánchez, Verónica; Castro-Piñero, José
Abstract: Objectives: The current study aimed at analyzing the associations between latent transitions based on sedentary time and physical activity levels and changes in Health-Related Quality of Life (HRQoL), positive affect, and negative affect over two years in children and adolescents. Design: Longitudinal design. Methods: Participants were 1099 children and adolescents (544 girls) aged 8–18 years old (11.72 ± 2.39 years). Sedentary and physical activity levels were assessed by accelerometry. Well-being was approached through self-reported HRQoL, positive affect, and negative affect. Latent profile and latent transition analysis were developed at baseline and 2-year follow-up. Furthermore, we analyzed the cross-sectional relationship between lifestyle profiles and well-being, as well as the associations between profiles transitions and changes in well-being indicators. Results: Four profiles were identified at both time-points, respectively: highly sedentary (7.7% and 8.3%), sedentary (34.4% and 35.9%), active (46.3% and 44.3%), and highly active (11.6% and 11.5%). Participants belonging to the highly active profiles showed better HRQL (p < 0.05 at both timepoints) than sedentary participants, and better positive affect (p < 0.05 at follow-up) than those in sedentary and active profiles. Lifestyle profiles were unstable to moderate stable, where sedentary and active profiles were the most stable patter (63.7% and 61.9%, respectively), and highly sedentary and highly active were the least (34.1% and 38.3%, respectively). Changing from an active to a sedentary profile was associated with a significantly greater decrease on the positive affect than keeping on active or changed from a sedentary to an active profile, whereas changing to an active profile attenuated the decrease in HRQoL. Conclusions: This study identified lifestyle profiles transitions among young population, and demonstrates the importance of these behaviors patterns on well-being indicators. These findings suggest the development of practical interventions aimed at promoting healthy lifestyles (i.e., increasing PA and reducing ST) in those youth with sedentary profiles, which will cause an increase on feelings of well-being. Highlights: Four profiles were found (highly sedentary, sedentary, active, and highly active). Active profiles were associated with better HRQoL and positive affect. Lifestyle profiles were unstable to moderate stable, ranging from 34.1% to 63.7%. Changing to a sedentary profile caused a greater decrease on positive affect. Changing to an active profile attenuated the decrease in HRQoL.